2017
DOI: 10.1136/gutjnl-2016-313654
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue macrophages induce hepatic neutrophil recruitment and macrophage accumulation in mice

Abstract: ATMs from obese vAT induce hepatic macrophage accumulation during NASH development, possibly by enhancing neutrophil recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 37 publications
5
78
0
Order By: Relevance
“…ATMs especially release a high amount of neutrophil chemotactic proteins that increase neutrophil recruitment liver and worsen liver injury 42 . Indeed, clinical studies reported a significant correlation of ATMs with neutrophil and macrophage content in liver biopsies 43 as well as with steatosis severity and fibrosis indexes 44 . The crosstalk between liver and adipose tissue also involves the adipocytokines.…”
Section: Fatty Liver Disease: Crosstalk With Surrounding Tissuesmentioning
confidence: 99%
“…ATMs especially release a high amount of neutrophil chemotactic proteins that increase neutrophil recruitment liver and worsen liver injury 42 . Indeed, clinical studies reported a significant correlation of ATMs with neutrophil and macrophage content in liver biopsies 43 as well as with steatosis severity and fibrosis indexes 44 . The crosstalk between liver and adipose tissue also involves the adipocytokines.…”
Section: Fatty Liver Disease: Crosstalk With Surrounding Tissuesmentioning
confidence: 99%
“…As mentioned previously, impaired suppression of insulin-mediated lipolysis in white adipose tissue (WAT) leads to hepatic steatosis through increased fatty acid uptake of hepatocytes (Figure 1). In addition, inflammation in WAT systemically affects hepatic inflammation (74). Lean mice transplanted with visceral adipose tissue from obese mice exhibited elevated infiltration of neutrophils and macrophages in the liver and ultimately suffered from aggravated liver damage after NASH diet feeding (74).…”
Section: “Multiple-parallel Hit” Pathogenesis Of Nashmentioning
confidence: 99%
“…In addition, inflammation in WAT systemically affects hepatic inflammation (74). Lean mice transplanted with visceral adipose tissue from obese mice exhibited elevated infiltration of neutrophils and macrophages in the liver and ultimately suffered from aggravated liver damage after NASH diet feeding (74). However, transplantation of visceral fat from obese mice with depletion of adipose tissue macrophage (ATM) by treatment with clodronate liposomes did not cause hepatic inflammation in lean mice (74), suggesting that ATM directly contributes to hepatic inflammation and NASH progression.…”
Section: “Multiple-parallel Hit” Pathogenesis Of Nashmentioning
confidence: 99%
See 1 more Smart Citation
“…Bijnen et al 2 expand on the role of AT inflammation and its effects on NAFLD, investigating how AT inflammation contributes to immune cell recruitment to the liver. The first indication that inflammatory CD11c + ATMs impacted on liver immune cell populations came by identifying a positive correlation between the abundance of CD11c + ATMs and liver macrophages in obese mice.…”
mentioning
confidence: 99%